Um Estudo Contrastivo de Línguas Tupi: Araweté, Kamaiurá, Aweti e Sateré-Mawé - Spoladore, Fernanda Ferreira (2017)
The aim of this work, composed of eight chapters, is to present a comparative study of nominal and verbal constructions of four Tupi trunk languages, as well as their independent sentences. Strictly synchronic, it includes Araweté and Kamaiurá languages, two members of Tupi-Guarani family, as well as Aweti and Sateré-Mawé, unique members of its families, in order to point out their similarities and differences. This study, in which it is not proposed to describe these languages, is based on descriptive proposals already made. In the first chapter, we present the purpose and justification of this work. In the second chapter, we bring some historical, demographic and sociolinguistic considerations in relation to Araweté, Kamaiurá, Aweti and Sateré-Mawé people. In the third chapter, we present some considerations about Contrastive and Typological Linguistics, as well as theoretical perspectives of Structural Functionalism and Enunciation. After that, we discuss the sentences of nonverbal and verbal predicate in natural languages. In the fourth chapter, in turn, we present the names and verbs of Araweté, Kamaiurá, Aweti and Sateré-Mawé, compared in morphosyntactic and semantic levels. In the fifth chapter, we expose the structure of postpositional and noun phrases in these languages, as well as function they can play in the sentences. In the sixth and seventh chapters, in turn, we propose a contrast of nonverbal and verbal predicate sentences. Finally, in the eighth chapter, we present the final considerations of this work.